Pharmacological characterization of novel synthetic opioids (NSO) found in the recreational drug marketplace. (15th May 2018) - Baumann, Michael H.; Majumdar, Susruta; Le Rouzic, Valerie; Hunkele, Amanda; Uprety, Rajendra; Huang, Xi Ping; Xu, Jin; Roth, Bryan L.; Pan, Ying-Xian; Pasternak, Gavril W.
Abstract: Novel synthetic opioids (NSO) are increasingly encountered in illicit heroin and counterfeit pain pills. Many NSO are resurrected from older biomedical literature or patent applications, so limited information is available about their biological effects. Here we examined the pharmacology of three structurally-distinct NSO found in the recreational drug market: N- (1-(2-phenylethyl)-4-piperidinyl)- N -phenylbutyramide (butyrylfentanyl), 3, 4-dichloro- N -[(1R, 2R)-2-(dimethylamino)cyclohexyl]- N -methylbenzamide (U-47700) and 1-cyclohexyl-4-(1, 2-diphenylethyl)piperazine (MT-45). Radioligand binding and GTPγS functional assays were carried out in cells transfected with murine mu- (MOR-1), delta- (DOR-1) or kappa-opioid receptors (KOR-1). Antinociceptive effects were determined using the radiant heat tail flick technique in mice, and opioid specificity was assessed with the mu-opioid antagonist naloxone. Butyrylfentanyl, U-47700 and MT-45 displayed nM affinities at MOR-1, but were less potent than morphine, and had much weaker effects at DOR-1 and KOR-1. All NSO exhibited agonist actions at MOR-1 in the GTPγS assay. Butyrylfentanyl and U-47700 were 31- and 12-fold more potent than morphine in the tail flick assay, whereas MT-45 was equipotent with morphine. Analgesic effects were reversed by naloxone and absent in genetically-engineered mice lacking MOR-1. Our findings confirm that butyrylfentanyl, U-47700 and MT-45 are selective MOR-1 agonists with in vitro affinities less than morphine. However, analgesic potencies vary more than 30-fold across the compounds, and in vitro binding affinity does not predict in vivo potency. Taken together, our findings highlight the risks to humans who may unknowingly be exposed to these and other NSO when taking adulterated heroin or counterfeit pain medications. This article is part of the Special Issue entitled 'Designer Drugs and Legal Highs.' Graphical abstract: Highlights: Novel synthetic opioids (NSO) are found in heroin products and counterfeit pain pills. Butyrylfentanyl, U-47700 and MT-45 are NSO that bind to mu-opioid receptors. Butyrylfentanyl and U-47700 are much more potent than morphine as analgesic agents. The in vitro affinities of NSO at mu-opioid receptors may not predict in vivo potencies. NSO present a public health risk to those unknowingly exposed to these drugs.